Exercise for endurance and strength: always separate? - Gronek, Piotr; Kryściak, Jakub; Clark, Cain C.T.; Stroińska, Weronika (Akademia Wychowania Fizycznego w Poznaniu)
Physical training can be classified into three main types: endurance, resistance, and patterned movements. The first two of them have a significant impact on muscle phenotype and metabolism while patterned movement exercises concern changes in a motor program in the central nervous system and result in only slight changes in muscle tissue. Adaptation to endurance versus resistance training in most aspects is extremely different. Due to the mutually opposite nature, in classical training systems, endurance and resistance exercises are very often separated. Nowadays, in sport as well as recreation and rehabilitation it is postulated to combine both types of exercises. Because of this, the very important question arises as to how combined workouts including strength and endurance exercises will affect the body. An even more important question concerns the proportions of both types of exercises, their intensity and duration. Therefore, defining safe and effective training systems can be beneficial not only for athletes but also for the prevention of civilization-related diseases and aging effect
Keywords: endurance training; resistance training; combined training; aging